2008
DOI: 10.1063/1.2842365
|View full text |Cite
|
Sign up to set email alerts
|

Centrifugally driven electrostatic instability in extragalactic jets

Abstract: The stability problem of the rotation induced electrostatic wave in extragalactic jets is presented. Solving a set of equations describing dynamics of a relativistic plasma flow of AGN jets, an expression of the instability rate has been derived and analyzed for typical values of AGNs. The growth rate was studied versus the wave length and the inclination angle and it has been found that the instability process is much efficient with respect to the accretion disk evolution, indicating high efficiency of the in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…To study the generation of extremely unstable Langmuir waves, we follow the method developed in (Machabeli et al 2005;Osmanov 2008). Throughout the paper, we assume that the magnetic field lines are almost straight and lie in the equatorial plane.…”
Section: Centrifugal Excitation Of Langmuir Wavesmentioning
confidence: 99%
See 1 more Smart Citation
“…To study the generation of extremely unstable Langmuir waves, we follow the method developed in (Machabeli et al 2005;Osmanov 2008). Throughout the paper, we assume that the magnetic field lines are almost straight and lie in the equatorial plane.…”
Section: Centrifugal Excitation Of Langmuir Wavesmentioning
confidence: 99%
“…In this paper, we go back to reexamine the problem begun in (Osmanov 2008); we will investigate the efficiency of centrifugally driven electrostatic waves in the AGN magnetosphere, and determine if these waves can be a conduit for transferring energy towards particle acceleration. In contrast to the pulsars, the AGN atmosphere contains a quasineutral plasmas composed of protons and electrons, Consequently the mass dependent centrifugal force acting will produce an initial charge separation on electrons and protons, leading, perhaps, by means of the parametric instability, to extremely efficient energy pumping from the rotating magnetosphere.…”
Section: Introductionmentioning
confidence: 99%
“…In this section we consider a slightly moderate mechanism of acceleration. In particular, in [6,7] we have shown that rotation energy might be very efficiently pumped into that of Langmuir waves. On the next stage, under certain conditions, energy of electrostatic modes might be converted into energy of plasma particles.…”
Section: Acceleration Via Damping Of Centrifugally Excited Langmmentioning
confidence: 97%
“…This method was applied to AGN jets in Ref. 9 and the stability problem of the rotation-induced electrostatic waves has been studied. The CF is significant also for inducing the CDI.…”
Section: Introductionmentioning
confidence: 99%